1994
DOI: 10.1093/jnci/86.8.614
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel Density and Distribution in Ductal Carcinoma In Situ of the Breast

Abstract: DCIS of the breast is characterized by two patterns of stromal microvessels. The first pattern is a diffuse increase in stromal microvessels surrounding involved spaces. This pattern is particularly prominent in comedo-type lesions with marked stromal desmoplasia. The second pattern is microvessel cuffing of involved spaces that is present in only a minority of cases and appears unrelated to histologic features evaluated, including DCIS subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
150
2
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(166 citation statements)
references
References 0 publications
10
150
2
4
Order By: Relevance
“…There was also a significant negative correlation between vascular density and both the cross-sectional areas of the ducts involved and the extent of the necrosis of the tumour they contained. The last finding is in apparent conflict with the study of Guidi et al (1994), who found that comedo-type lesions were more likely to be associated with higher microvessel density. In their study, however, vessels up to 500 mm from the involved structures were included and only those from the five most vascular fields were recorded.…”
Section: Mvd (Vessels MMcontrasting
confidence: 60%
See 2 more Smart Citations
“…There was also a significant negative correlation between vascular density and both the cross-sectional areas of the ducts involved and the extent of the necrosis of the tumour they contained. The last finding is in apparent conflict with the study of Guidi et al (1994), who found that comedo-type lesions were more likely to be associated with higher microvessel density. In their study, however, vessels up to 500 mm from the involved structures were included and only those from the five most vascular fields were recorded.…”
Section: Mvd (Vessels MMcontrasting
confidence: 60%
“…We therefore felt that it was reasonable to hypothesize that changes in periductal vascularity may precede the development of invasive carcinoma in DCIS. Two patterns of angiogenesis have been described in DCIS: a diffuse stromal vascularity (pattern I) and a vascular rim around the involved ducts (pattern II) (Guidi et al, 1994). Subsequently, it was proposed that pattern II resulted from angiogenic factors secreted by tumour cells and pattern I from recruitment of accessory cells, which release angiogenic factors (Engels et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of vessels in the stroma between normal breast ducts was used as a reference in each case. We also noted if there was a dense rim of microvessels adjacent to the basement membrane of DCIS ducts (cuffing phenomenon) as earlier described by Guidi and by Engels (Guidi et al, 1994;Engels et al, 1997). The cuffing phenomenon was scored as present (defined as microvessels completely surrounding one involved duct or surrounding at least 50% of 2 or more involved ducts) or absent.…”
Section: Methodsmentioning
confidence: 97%
“…A key role for VEGF in tumour biology is supported by observations of production by numerous tumour cell lines (Senger et al, 1983(Senger et al, , 1986 and immunohistochemical demonstration in human carcinomas of several tissues, including breast Anan et al, 1996), lung (Mattern et al, 1996), liver , gastrointestinal tract (Brown et al, 1993b;Takahashi et al, 1995;Maeda et al, 1996), bladder (Brown et al, 1993a, O'Brien et al, 1995, kidney (Brown et al, 1993a;Sato et al, 1994;Takahashi et al, 1994) and ovary (Boocock et al, 1995; Abu-Jawdeh et al, (Toi et al, 1993;Guidi et al, 1994;Toi et al, 1994;Takahashi et al, 1995) and between VEGF expression and prognosis in breast, gastric and bladder cancer (O'Brien et al, 1995). Use of neutralizing antibodies to VEGF or transfection with antisense VEGF cDNA have been shown to result in inhibition of growth of tumour cell lines in nude mice and inhibition of metastatic spread (Asano et al, 1995;Warren et al, 1995;Claffey et al, 1996;Saleh et al, 1996).…”
mentioning
confidence: 87%